Pelatihan Teknologi Tepat Guna Bagi Kelompok Usaha Pengrajin Bambu di Kota Kendari - La Hasanudin; Aminur; Sudarsono; Ridway Balaka; Samhuddin; Citra Yurnidarsyah (Indonesian Journal of Community Services, 2022)
The abundance of bamboo prompted both partners Sri Jeki and Bambu Apus to set up a bamboo craft business in Kendari city. As the business goes on, the demand for various bamboo works continues to increase. Both craftsmen experienced difficulties in meeting production targets. So far, craftsmen only use machetes to split, sharpen, and thin bamboo in their production activities. The solution offered in this service activity is to introduce and provide appropriate technology training for bamboo defenders to accelerate and increase the production of bamboo crafts. The method of this activity is to train craftsmen in using appropriate technology for bamboo defenders to accelerate and increase the production capacity of bamboo crafts. The results obtained from this service activity are that the craftsmen can use the right technology for bamboo splitting tools safely and quickly so that their productivity increases.